A qualitative study on determinants of choice of contraceptives in a rural - Swamy, Hamsa T.; M., Bhanu; B. S., Nanda Kumar; N. S., Shivaraj (International Journal Of Community Medicine And Public Health, 2017)
Background: Family planning is a fundamental right of every human being. According to National Family Health Survey-4 Karnataka factsheet the rate of female sterilization is 48.6%, as compared to 57.4% in the NFHS-3 survey.1 Further as per NFHS-4 the rate of male sterilization is 0.1%, IUD/PPIUCD is 0.8%, pill use is 0.4%, and condom use is 1.3%. This study aims to determine factors influencing contraceptive non-use among women aged 15 - 49 years in rural area, Karnataka. Methods: Three focus group discussions were conducted in Ardesahalli Primary Health Center area to assess the knowledge and attitude of the women with regards to use and determinants for choices of contraceptives. Conceptual framework was used to develop the leading questions for the focus group discussions which included macro and micro level factors determining use or non-use of contraceptives. Results: Mother-in-law’s lack of knowledge about contraceptive use and fear of side effects regarding contraceptive had an influence on daughter and daughter-in-law’s for using/not using any method. Conclusions: Similar qualitative studies revealed that there were personal, cultural, and health system barriers to modern contraceptive use. In our study also Mother-in-law’s lack of knowledge and fear of side effects regarding contraceptive had an influence on daughter-in-law’s. It is imperative that the entire family is involved during the counseling sessions so that the misconceptions and irrational beliefs are addressed comprehensively.